The Effect of Foreign Direct Investment and Official Development Assistance to Human Development Index of Developing Countries at 2009-2013 - Agusty, Gerry Julian; Damayanti, Sylviana Maya (Journal of Business and Management, 2015)
Abstract. Foreign Direct Investment (FDI) occurs whenÂ  a foreign firm from particular country invest in foreign country in purpose to develop their business even more global, meanwhile Official Development Assistance (ODA) is another type of capital source that formed in loan in which will be given to the countries in DCA list. These two types of capital source have been playing important role in supporting development and human welfare in developing countries around the world. The human welfare dan development will be measured by Human Development Index (HDI) since this measurement is able to cover all aspects to measure human welfare and development in which have 3 dimensions: health that is measured by life expectancy, education that is measured by the education level achieved, and the last is the standard of living dimension that is measured by GNI per capita. The ODA inward amount alone that flow to developing countries for 2009-2013 reach the number of 700 million dollars, meanwhile the flow FDI reach the number of 5 billion dollars. This fantastic amount of money indicates that the demand for capital sources from foreign countries is still considered high. The tools that will be applied to find the effect of FDI and ODA is panel data regression analysis with purposive sampling to choose 124 countries as the samples. The findings of this research are: 1. FDI and ODA are proven to have significant effect to Human Development Index simultaneously 2. FDI and ODA are proven to have positive significant effect to Human Development Index partially with the number of R2 reaches 99% meaning that FDI and ODA can explain strongly its variance of HDI. This research can also be useful to consider the right type of capital sources or investmet that should be taken by a country in supporting development.Â Keywords:Foreign Direct Investment, Official Development Assistance, Developing Countries, Human Development Index, Statistics